PERANCANGAN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU BERBASIS WEB PADA UPT SPF SDN 31 BONTOMACINNA - Haerana Haerana; Adi Candra; Andi Nurul Faizah (Institut Teknologi dan Bisnis Bina Adinata, 2024)
This research aims to: (1) Designing a New Student Admission Information System at UPT SPF UPT SPF SDN 31 Bontomacinna. (2) Implementing the Design of the New Learner Admission Information System at UPT SPF SDN 31 Bontomacinna. Based on these problems, the new student admission system is a solution where the new student admission system is useful for making it easier to register new students. This research uses the Waterfall method. In this method there are six stages, namely, Analysis, Design, Coding, Testing, Implementation and Maintenance. Based on the results of the study showed that: (1) This web-based new student admission is designed and built based on the problems that occur in the process of admitting new students in designing information systems using the Unified Modeling Languange (UML). (2) The system application used is XAMPP, as well as the Hypertext Prepocessor Programming language (PHP) and MySQL. (3) The testing carried out in this system is using the Black Box method. This study produces a New Learner Admission Information System Design at UPT SPF SDN 31 Bontomacinna, in this study using an instrument in the form of a questionnaire to determine the user's response, namely the New Learner Admission committee at UPT SPF SDN 31 Bontomacinna. Based on the response of the New Student Admission committee UPT SPF SDN 31 Bontomacinna, where the system as a whole and the completeness of its features match what is needed which can be accessed easily. The value obtained from data analysis is 90% with a very positive category, meaning that it is feasible to use.